State of the world : innovations for a sustainable economy - Starke, Linda (ed.) (London, 2008)
The environmentalist's bible' Times Higher Education Supplement. 'Essential reading' The Good Book Guide. 'The most comprehensive, up-to-date, and accessible summaries ... on the global environment' E. O. Wilson, Pulitzer Prize winner. Celebrating its 25th year of publication, State of the World 2008 suggests that something huge and even revolutionary is struggling to be born as policymakers, business leaders and others around the globe create the architecture of sustainable economies. Featuring chapters on renewable energy, innovations in clean production, commons resources, trade policy, finance for sustainability, new economic yardsticks, and many other topics, State of the World 2008 is the first global-level publication to showcase a wide range of diverse innovations and to demonstrate their near-term potential to put whole societies on a sustainable path. Published annually in 28 languages, State of the World is relied upon by national governments, UN agencies, development workers and law-makers for its authoritative and up-to-the-minute analysis and information. It is essential for anyone concerned with building a positive, global future.
Keywords: Sustainable society